Investigation of the relationship between serum endocan level and interleukin-6, procalcitonin, e-selectin in calves with diarrhea, according to the etiological factor - Unal, Cennet Nur; Issi, Mustafa (Elsevier, 2025)
This study aimed to investigate the association between endothelial damage and inflammatory biomarkers interleukin-6 (IL-6) and procalcitonin (PCT) by evaluating the endothelial markers endocan and E-selectin in cases of calf diarrhea. The study population comprised 49 calves (42 with diarrhea and 7 healthy controls). Blood samples were collected from the diarrheic calves on the 7th and 10th days following diagnosis. Treatment was initiated after the first round of blood sampling. In within-group comparisons, the initial measurements revealed significantly elevated levels of endocan and PCT in the E. coli group compared to the measurements taken on the 7th and 10th days. In between-group comparisons, significant differences were observed between the E. coli and control, rotavirus and control, and C. parvum and control groups. The infected groups exhibited markedly higher levels of endocan on days 1, 7, and 10, and elevated IL-6 levels on day 1. Additionally, E-selectin levels were significantly elevated in the infected groups on day 1, with statistically significant differences noted between the E. coli and control groups, as well as the C. parvum and control groups. PCT level was higher in the infected groups on day 1, but there was a significant difference between E. coli and Control, Rotavirus and Control groups. In conclusion, inflammation and endothelial damage were determined in calves infected with E. coli, Rotavirus, and C. parvum. There was also a positive correlation between inflammation and endothelial damage. According to the data obtained, it was concluded that endocan and E-selectin may be useful biomarkers in determining endothelial damage in calves with diarrhea.
Keywords: Calf Diarrhea; Endocan; Endothelium; Inflammation